Avoiding overheating in existing school buildings through optimized passive measures. Issue 4 (18th May 2020) - Camacho-Montano, Sandra Carolina; Cook, Malcolm; Wagner, Andreas
ABSTRACT: The retrofitting strategies in European school buildings are usually focused on reducing the heating demand since it represents the major energy consumption. Nevertheless, the rise in outdoor temperatures shows that the risk of overheating during the summer is increasing. When planning such processes, decision-makers need to take into account the different building typologies, the effect of the potential measures in the future conditions and their costs. This study integrates these factors and provides specific guidance on the most appropriate measures to improve indoor thermal comfort in classrooms in the city of Karlsruhe, Germany. The simulations suggested that current overheating of the studied buildings represents up to 27% of the occupied time. The heavyweight buildings could prevent overheating by means of good ventilation, while lightweight buildings require more sun protection. With the appropriate natural ventilation strategy and with the help of ceiling fans, overheating can be avoided in most of the building types in the near future. In the case of lightweight buildings, overheating can be reduced to less than 10% of discomfort during occupied time; however, it would be required to significantly reduce the solar gains through technologies such as electrochromic glazing or a combination of other passive measures.